Influence of MHD Lubrication and Textured Surface in EHL Line Contact - Jadhav, Suresh; Thakre, Gananath D.; Sharma, Satish C. (Frontiers in Mechanical Engineering, 2019)
The present numerical study investigates the combined effect of micro-texture and magneto hydrodynamic lubrication behaviour on the performance of EHL line contact. Micro-textures are provided in the inlet zone of contacting surface has been studied. Modified Reynolds equation, elasticity equation and load balance equation has been solved using FEA and Generalized Minimal Residual Method (GMRES). A parametric study has been performed to optimize the micro-texture shapes in the contacting surfaces for different values of magneto hydrodynamic lubricant parameters The numerical results show that increasing externally applied magnetic field and micro- texture shapes enhances the values of performance parameter of EHL line contact. Finally, the variation in the steady-state EHL characteristics pertaining to unidirectional pure sliding contacts due to an artificially produced IZMTS is investigated numerically. The enhancement in central and minimum film thickness is found to be upto 38% and 28% respectively along with 33.28% reduction in coefficient of friction.